Перспективи використання біофільтрів у біогазових установках - Скляр, Олександр Григорович; Skliar, Oleksandr; Скляр, Радміла Вікторівна; Skliar, Radmila; Болтянський, Борис Володимирович; Boltianskyi, Borys; Сиротюк, С. В.; Коробка, С. В. (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті розглянуто сучасний стан переробки гнойових стоків у метантенках із біофільтрами, що забезпечують покращене зброджування органічної маси завдяки штучному накопиченню метаноутворювальних мікроорганізмів. Проаналізовано вплив біофільтрів на стабілізацію процесів метаногенезу, розширення діапазону рН і температурних режимів, що сприяє підвищенню ефективності біогазових установок. Визначено основні вимоги до матеріалів біофільтрів та методи їх використання. Досліджено перспективи застосування анаеробних біофільтрів у біогазових технологіях для різних типів органічної сировини. /// EN: The article deals with the current state of manure wastewater processing in digesters with biofilters that provide improved fermentation of organic matter due to the artificial accumulation of methane-forming microorganisms. The influence of biofilters on the stabilization of methanogenesis processes, expansion of the pH range and temperature conditions, which contributes to the efficiency of biogas plants, is analyzed. The basic requirements for biofilter materials and methods of their use are determined. A biofilter is one of the main elements of a cooperative biogas plant, where a biofilm is formed mainly from an association of anaerobic microorganisms that decompose organic matter and convert it into methane, hydrogen, and carbon dioxide without oxygen. The advantage of such biofilters, compared to aerobic ones, is lower electricity consumption and biogas production. The prospects for the use of anaerobic biofilters in biogas technologies for different types of organic raw materials are investigated. The prospects for the use of biofilters in biogas plants are considered: creating favorable conditions for the development of methaneforming microorganisms, increasing the energy efficiency of biogas plants, expanding the range of raw materials for fermentation, environmental benefits and reducing harmful emissions, extending the life of digesters and reducing the need for equipment cleaning, the possibility of integrating biofilters into industrial and municipal biogas projects. The use of biofilters in biogas plants helps to improve the performance of the anaerobic digestion process, reduce operating costs, expand the raw material base, and reduce the environmental burden. The introduction of biofiltration technologies into biogas complexes in Ukraine can become one of the key areas for improving bioenergy and contribute to the country’s energy independence.
Prospects for the use of biofilters in biogas plants
Keywords: біогаз; анаеробне зброджування; метантенк; переробка; органічні відходи; метаногенез; biogas; anaerobic digestion; digester; processing; organic waste; methanogenesis